A simulation model for the mixed traffic system in Vietnam. (22nd January 2010) - Le Ngoc, Quynh-Lam; Do, Ngoc-Hien; Nam, Ki-Chan
Simulation models have been used successfully to model traffic systems, test various traffic control algorithms and solve traffic problems in many developed countries. However, they are unlikely to produce reliable results if applied to Vietnam's mixed traffic conditions, where motorbikes are the principle means of transportation. This paper models and simulates the mixed traffic system. Accordingly, the traffic system is characterised and the logic of the simulation model is introduced briefly. In order to validate and demonstrate the usefulness of the simulation model, a case study is presented. Finally, some conclusions and suggestions are proposed.